Ehlers–Danlos Syndrome Caused by Biallelic TNXB Variants in Patients with Congenital Adrenal Hyperplasia. Issue 9 (8th July 2016) - Chen, Wuyan; Perritt, Ashley F.; Morissette, Rachel; Dreiling, Jennifer L.; Bohn, Markus‐Frederik; Mallappa, Ashwini; Xu, Zhi; Quezado, Martha; Merke, Deborah P.
Abstract : Biallelic TNXB variants in patients with congenital adrenal hyperplasia due to CYP21A2 deletions result in a classical Ehlers‐Danlos syndrome phenotype with skin hyperextensibility, widened atrophic scars and joint hypermobility. Reduced elastic fiber formation, shortened and disorganized fibrillin‐1 fibers and reduced collagen density are observed in dermal tissue. Modeling reveals that the TNXB variants interfere with the tenascin‐X fibrinogen‐like domain stability. The expansion of TNXB findings in patients with CAH widens our understanding of connective tissue dysplasias. ABSTRACT: Some variants that cause autosomal‐recessive congenital adrenal hyperplasia (CAH) also cause hypermobility type Ehlers–Danlos syndrome (EDS) due to the monoallelic presence of a chimera disrupting two flanking genes: CYP21A2, encoding 21‐hydroxylase, necessary for cortisol and aldosterone biosynthesis, and TNXB, encoding tenascin‐X, an extracellular matrix protein. Two types of CAH tenascin‐X (CAH‐X) chimeras have been described with a total deletion of CYP21A2 and characteristic TNXB variants. CAH‐X CH‐1 has a TNXB exon 35 120‐bp deletion resulting in haploinsufficiency, and CAH‐X CH‐2 has a TNXB exon 40 c.12174C>G (p.Cys4058Trp) variant resulting in a dominant‐negative effect. We present here three patients with biallelic CAH‐X and identify a novel dominant‐negative chimera termed CAH‐X CH‐3. Compared with monoallelic CAH‐X, biallelic CAH‐X results in a more severe phenotype with skin features characteristic of classical EDS. We present evidence for disrupted tenascin‐X function and computational data linking the type of TNXB variant to disease severity.